Utility of Condition Indices as Predictors of Lipid Content in Slimy Sculpin (Cottus cognatus) - Adrian R. Hards; Michelle A. Gray; Sophia C. Noël; Rick A. Cunjak (Diversity, 2019)
Slimy sculpin (Cottus cognatus) are increasingly being used as indicator species. This has primarily entailed measuring their condition, the assumption being that condition can be used as a surrogate for lipid content. While there is evidence to suggest this assumption is applicable to some fish, it has yet to be validated for C. cognatus. Further, there are several means by which one may calculate condition, the most commonly employed of which are indirect measurements of lipid content (namely, Fulton’s K, somatic K (Ks), and Le Cren’s relative condition factor (Kn)). We compared the ability of each of these morphometric indices to predict whole-body lipid content in C. cognatus. There was a moderate degree of evidence that Fulton’s K, Ks, and Kn are reliable predictors (Ks and Kn in particular). Of the latter we recommend Kn be used because, unlike Ks, it does not require that fish be killed. And while Fulton’s K did not perform quite as well, we consider it a sufficient substitute if the data necessary to calculate Kn are unavailable.